The European Union and the genesis of the space of cooperation in higher education and academic recognition community - Facundo Solanas (Arizona State University, 2014)
Besides its several nuances, the convergence process of higher education systems in the European Union countries and other twenty neighboring countries cannot be understood without evoking the experience gained by developing a set of programs implemented by the European Commission in the 80s. Regardless of the questions that can be raised about the "Bologna Process," it was promoted by the main Member States of the European Union, setting up the first actions on students' territorial mobility and academic recognition of study periods abroad. Based on some analysis tools originally coming from theoretical frameworks related to other political science sub-disciplines, such as sociology of public action and the europeanisation dynamics, this paper analyzes the genesis and importance of European cooperation policies on the higher education systems and looks for areas of convergence.